Accelerating digital transformation of SMEs - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2023)
Digital transformation is happening across all industries worldwide, including in Singapore. This book seeks to provide insights on how small and medium enterprises (SMEs) can embark on their own journeys of digital transformation, while at the same time remaining agile in responding to industry and consumer needs. It will outline how firms can foster a culture of business transformation to improve efficiency and productivity; elaborate on how the COVID-19 pandemic has accelerated the digital transformation process, and how it has provided new opportunities; present a roadmap on how SMEs can navigate through the artificial and data analytics revolution; and provide recommendations on how SMEs can partner with institutes of higher learning. It concludes by elaborating on the skillsets and capabilities needed to drive digitalisation.